The Eurozone: Piecemeal Approach to an Optimum Currency Area - Heinz Handler (Austrian Institute of Economic Research (WIFO), 2013)
Soon after the establishment of the Eurozone it became obvious that the structural differences between member countries would not abate, as expected, but rather gradually widen. Although part of the problem can be attributed to the enlargement process, it also relates to asymmetric effects of the common currency and to diverging economic policies. This paper discusses the literature which associates the economic characteristics of EMU with arguments of the optimum currency area (OCA) theory and asks for missing capstones that would meliorate EMU to eventually resemble an OCA. As potential candidates for such building blocks, some sort of fiscal union and lender of last resort may qualify, drawing on the experiences of other currency unions and federal states. The financial and debt crisis has revealed that the endogenous forces within a currency union may be too slow to absorb the shocks originating from the crisis. For a currency union to survive in such a situation it is all the more important that the OCA criteria are met and/or that complementary institutions are in place. However, as actual developments in the Eurozone reveal, the political process of approaching an OCA is piecemeal rather than comprehensive and prompt.
Keywords: 330; Eurozone; Optimaler Währungsraum; EU-Staaten